Effectiveness, Safety, and Predictors of Response to 5% Lidocaine-Medicated Plaster for the Treatment of Patients With Trigeminal Neuralgia: A Retrospective Study. Issue 5 (May 2023) - Yu, Bin; Zhang, Wei; Zhao, Chunmei; Xing, Yan; Meng, Lan; Luo, Fang
Background: Whether 5% lidocaine-medicated plaster (LMP) is a valuable therapeutic option for the treatment of trigeminal neuralgia (TN) is worth exploring. If LMP is proven effective for TN, positive predictors of the analgesic effects of LMP warrant further investigation. Objective: To evaluate the efficacy and safety of LMP for the treatment of TN, and to explore the predictive factors for the treatment efficacy of LMP. Methods: This is a retrospective and observational study. We analyzed the efficacy of LMP for the treatment of TN between March 2019 and January 2022. The follow-up time was approximately 2 weeks, 1 month, 2 months, and 3 months after LMP treatment. The LMP response was considered the Barrow Neurological Institute (BNI) score of I to III and an improvement in BNI of at least I grade from pretreatment baseline. Univariable and multivariable logistic analyses were performed to identify the predictive factors for LMP response. Results: A total of 103 patients were included and analyzed in this study. LMP was effective in some TN patients, with an efficacy rate of 21.4%, 21.4%, 18.4%, and 16.5% after 2 weeks, 1 month, 2 months, and 3 months of LMP treatment, respectively. The overall adverse event rate associated with LMP was 5.8%, and the reported adverse events were all skin reactions. Facial trigger points (odds ratio [OR] = 0.25, 95% confidence interval [CI] = 0.07-0.86, P = 0.03) and a lower BNI score (OR = 0.37, 95% CI = 0.07-0.87, P = 0.01) were identified as potential predictors for initial efficacy (2-week follow-up) of LMP treatment. Conclusions and Relevance: LMP has been shown to provide effective and sustained analgesia in some TN patients with minimal risk of systemic adverse reactions. Patients with facial trigger points and mild to moderate pain are more likely to benefit from LMP treatment. Our data suggest that LMP may be an effective treatment option for patients with the aforementioned characteristics of TN.